Synthesis report: Agricultural transformation and market integration in the ASEAN region: Responding to food security and inclusiveness concerns - Roy, Devesh; Kamar, Abul; Pradhan, Mamata; Saroj, Sunil (International Food Policy Research Institute, 2025)
The Association of Southeast Asian Nations (ASEAN) is a regional grouping of Southeast Asian countries formed in 1967 by Indonesia, Malaysia, the Philippines, Singapore, and Thailand. Brunei Darussalam joined this association in 1984. ASEAN expanded to 10 countries between 1995 and 1999 by extending memberships to Cambodia, Lao PDR, Myanmar, and Viet Nam. These 10 Southeast Asian countries entered into the trade agreement to ensure the free flow of goods, including agricultural products. Agreements related to services and investment were also signed to enhance economic cooperation and to develop an ASEAN Economic Community (AEC). The implementation of the ASEAN Free Trade Area (AFTA) in 2003 helped liberalize the intra-ASEAN agricultural trade, which grew steadily during the period under review. Further, the dynamics of intra ASEAN trade show that after the food price crisis of 2007/2008, intra-ASEAN agricultural trade increased sharply, which reflects ASEAN’s efforts to create a food security action plan aimed at improving sustainable food trade among ASEAN members.